Assessing Geospatial Accuracy in Mapping Applications: A Focus on Google Earth - Thaar Alqahtani (Salehan Institute of Higher Education, 2024)
Google Earth, among other online mapping platforms, offers an interactive mapping platform that has become indispensable for academic and research applications. It serves as a primary reference and a foundational tool for map creation, providing open-source, cost-free imagery that meets the user needs of the mapping community. As a contemporary repository of high-resolution images of Earth's landmass, Google Earth has vast potential for scientific exploration and remains an underexploited resource. Its rapid expansion and consistent reliability make it a favored source for mapping and routing tasks. However, this research underscores the crucial aspect of Google Earth's positional accuracy, which is at the heart of this study. A comparative analysis between the positional accuracy of Google Earth and traditional ground surveying maps was conducted. The Wilcoxon rank test and quantitative methods were used to evaluate coordinate discrepancies, revealing significant discrepancies between the two datasets. This study aims to provide a rigorous assessment of Google Earth's utility and accuracy in scientific and academic contexts, emphasizing its role and reliability as a critical resource for researchers and practitioners in the field of mapping. The results revealed displacement changes in both the northing and the easting coordinates. For the northing coordinates, the displacement increases when moving eastward and decreases when moving westward. For the easting coordinates, the displacement increases when moving northward and decreases when moving southward. This pattern highlights spatial discrepancies and the varying impact of location on the dataset's accuracy, emphasizing the need for targeted corrections to enhance data accuracy. These key findings provide valuable insights that could significantly contribute to optimizing mapping practices and efficiently exploiting this vast, yet underexplored, digital resource. Doi: 10.28991/CEJ-2024-010-08-012 Full Text: PDF